Synonymy of soil-feeding termites Pseudocapritermes sowerbyi and Pseudocapritermes largus, with evidence from morphology and genetics - Xuan, Ruoyue; Dai, Qingfeng; He, Can; Zhang, Dayu; Pan, Chengyuan (Journal of Asia-Pacific entomology, 2021)
[Display omitted] •Drawing of morphological characters for measurement on Pseudocapritermes.•Description and comparison of two species of Pseudocapritermes on morphological characters.•Sequencing and analysis of full-length genes of COI, COII, and 16S rRNA.•Confirmed the close relationship between Pseudocapritermes and Sinocapritermes. Pseudocapritermes Kemner is a termite group that constructs subterranean gallery systems in topsoil. This genus is distributed in the Oriental region and contains 18 species. Dependence on the morphological measurements of soldiers makes the taxonomy of Pseudocapritermes difficult. In this study, we compared morphological characters of soldiers and adults of P. largus and P. sowerbyi. In addition, three fulllength mitochondrial genes (COI, COII, and 16S rRNA) were sequenced from a total of eight P. largus and P. sowerbyi colonies. Morphological comparison of soldiers showed that P. largus is larger than P. sowerbyi, but there was overlap in some measurements. In adults, the morphological characters of P. largus were congruent with those of P. sowerbyi. Sequence alignments of COI, COII, and 16S rRNA revealed a high pairwise genetic identity (ranging from 99.64 to 100%) between the two species, which suggested that P. largus and P. sowerbyi are the same species. Molecular phylogenetic analysis based on COII revealed that Pseudocapritermes belongs to the Termes group having soldiers with asymmetrical snapping mandibles and is more closely related to Sinocapritermes than to other Termes group genera distributed in China. Morphological similarity and genetic identity indicate that P. largus is a junior synonym of P. sowerbyi.